The fiscal risk of local government revenue in the People's Republic of China - Ziying Fan; Guanghua Wan (Asian Development Bank Institute (ADBI), 2016)
Since the Tax Sharing Reform in 1994, the local government revenue of the People's Republic of China (PRC) has faced downward risk problems. This paper reviews the fiscal and taxation reforms in the central and local governments of the PRC and focuses on evaluating the effectiveness of fiscal transfers. We find that, to a certain extent, fiscal transfers significantly promote the construction of local infrastructure. Earmarked transfers had an effect, but lump-sum transfers did not. Results showed every 1% increase in earmarked transfers to be associated with a 5% increase in local spending on infrastructure. These fiscal transfers also increased the size of local government spending such that a 1% increase of fiscal transfer would increase the ratio of local fiscal spending to gross domestic product by 1%. The risk of the local fiscal revenue sources was also assessed, and results showed that land finance, local government bonds, and fiscal transfers from the central government are not sustainable in the long term. The local fiscal system in the PRC needs to focus on improving local taxes in the future, such as the property tax.
Keywords: H71; H54; H68; 330; PRC fiscal risk; fiscal transfers; fiscal and tax reforms